PENGARUH MEDIA LEAFLET TERHADAP PENGETAHUAN IBU TENTANG IMUNISASI DASAR - Dhimas Herdhianta; Muhammad Rifqi Assafa; Hesty Damayanti Saleh (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2023)
Background: Immunization is a public health effort that can prevent transmission of several diseases. The proportion of complete basic immunization in children aged 12-23 months in East Java Province is categorized with complete immunization coverage of 69.2%, incomplete immunization of 26.3% and no immunization of 4.6%. Data in Pamekasan Regency with complete immunization is 37.5% and incomplete immunization is 41.93%. Therefore, it is necessary to intervene using leaflet health promotion media regarding basic immunization. The purpose of the study was to determine the effect of leaflet education media on maternal knowledge about basic immunization. Method: This study used pre-experimental with one group pretest-posttest design. The sample was visitors to the Penaguan Health Center as many as 32 respondents. The sampling technique used perposive sampling method. Data analysis using the Wilcoxon test. Result: The percentage of knowledge before being given education using leaflets is 46.56%. The percentage of knowledge after being given education using leaflets is 69.84%. The difference in knowledge increase was 23.28%. While the percentage increase in knowledge is 50%. The p value before and after being given education with leaflet media is p=0.000 (p<0.5). Conclusion : There is an effect of leaflet education media on maternal knowledge about basic immunization.